Screening of the active Ingredients in Huanglian Jiedu decoction through amide bond-Immobilized magnetic nanoparticle-assisted cell membrane chromatography - Liao, Fengyun; He, Dongmei; Vong, Chi Teng; Wang, Lisheng; Chen, Zhangmei; Zhang, Tiejun; Luo, Hua; Wang, Yitao (Frontiers in Pharmacology, 2022)
The Huanglian Jiedu decoction (HLJDD) is a Chinese herbal formula that exerts neuroprotective effects by alleviating oxidative stress injuries and may potentially be prescribed for treating Alzheimer's disease; however, its active ingredients have not yet been identified. Cell membrane chromatography is a high-throughput method for screening active ingredients, but traditional cell membrane chromatography requires multiple centrifugation steps, which affects its separation efficiency. Magnetic nanoparticles are unparalleled in solid–liquid separation and can overcome the shortcomings of traditional cell membrane chromatography. In this study, the neuroprotective effects of the components of HLJDD were screened through a novel magnetic nanoparticle-assisted cell membrane chromatography method. Magnetic nanoparticles and cell membranes were stably immobilized by amide bonds. This method was found to be stable, and the magnetic nanoparticles significantly improved the solid–liquid separation efficiency. Magnetic bead-immobilized cell membranes of HT-22 cells were incubated with the HLJDD extract to isolate specific binding components. They were then identified by ultraperformance liquid chromatography (UPLC)–Orbitrap Fusion Tribrid MS after solid-phase extraction. The bioactivity of these components was analyzed in an HT-22 cellular model of glutamate-induced injury. Fifteen of these components were found to specifically bind to the cell membranes, and seven of them were confirmed to reduce varying degrees of glutamate-induced toxicity in HT-22 cells. In conclusion, our findings suggest that the amide bond-based immobilization of magnetic nanoparticles on cell membranes, along with solid-phase extraction and UPLC, is an effective method for isolating and discovering the bioactive components of traditional Chinese medicines.